Potencial turístico gastronómico del cantón La Maná de la provincia de Cotopaxi. - Cerezo Loor, Jennifer Nayely (2024)
This research project was developed in La Maná, being one of the seven cantons that make up the Cotopaxi province, determining the gastronomic tourism potential of La Maná canton was the objective, it was carried out through the methodology of gastronomic elaboration maps (MINTUR) and SIGAP, where there are twelve registered dishes and two obtained in the field trip were identified, which were qualified using four criteria (history and tradition, local ingredients, current tradition and offer in the destination). each with a rating of 25 points resulting in 100 points according to the methodology. Most of the dishes have an average of 25 to 75 points, referring to a low potential for gastronomic tourism at La Maná canton, which determines that the study area has two of its own dishes that are not registered, these are only prepared in rural parishes. Next, population was taken into account through three groups, an intentional sample was chosen for authorities and service providers, and a probabilistic sample of 378 tourists. There it was verified that the current and potential profile of La Maná. It is the nature tourism with the greatest demand by national tourists whose main activity is the natural areas and waterfalls tour. In the activities course, the interest is born to taste the gastronomy that is offered and learnt more about the origin and the products that are used for preparation. Finally, a proposal for an academic article was prepared as a means of disseminating the research, which facilitates the results dissemination through a short communication, contributing to the new knowledge creation and at the same time enabling new researchers to put into practice. Talking with other contributions for greater academic advancement and generate questions for the research contributions generation. According to the study developed, a map was not made because the dishes registered in the canton are not considered potential because they are dishes originating from other provinces, therefore, they are not emblematic for the gastronomic map preparation of the canton